Education on Vegetable and Fruit Processing to Keep Maintaining Nutritional Levels in Benangkah Village, Burneh, Bangkalan - Alvia Nur Layli; Rika Yatun Nikmah; Indah Fadila Ulfa; Teguh Setiawan Wibowo (Jurnal Pengabdian Masyarakat Formosa, 2023)
The purpose of this activity is to increase participants' knowledge about the correct processing techniques for vegetables and fruit to maintain nutrient content. Furthemore, increase participant awareness to consume vegetables and fruit to meet daily nutritional requirements. This activity consists of four stages. First, the introduction of the situation. At this stage the committee conducts a regional survey and then determines the problem, then the activity targets are known. The second is planning, this consists of performance formation and preparation activity program. The third is implementation of activities and the last is assessment. This activity was carried out on January 27 2023. The community was enthusiastic about this activity and began to open their awareness about caring for their health.